A novel ECC-based lightweight authentication protocol for internet of things devices. (8th November 2019) - Tewari, Aakanksha; Gupta, B.B.
In spite of being a promising technology which will make our lives a lot easier we cannot be oblivious to the fact IoT is not safe from online threat and attacks. Thus, along with the growth of IoT we also need to work on its aspects. Taking into account the limited resources that these devices have it is important that the security mechanisms should also be less complex and do not hinder the actual functionality of the device. In this paper, we propose an ECC based lightweight authentication for IoT devices which deploy RFID tags at the physical layer. ECC is a very efficient public key cryptography mechanism as it provides privacy and security with less computation overhead. We also present a security and performance analysis to verify the strength of our proposed approach. We have verified the security and authentication session execution of our protocol using the Promela model and SPIN tool.